1996
DOI: 10.1159/000121097
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Skull Base Technique to the Repair of Transsphenoidal Meningoencephaloceles

Abstract: A 2-month-old boy with an anterior basal meningoencephalocele of the transsphenoidal type was successfully treated via the transbasal intra- and extradural approach. Magnetic resonance imaging was useful for obtaining a precise diagnosis, and the transbasal combined approach is suitable for this type of meningoencephalocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In humans, various types of meningoencephalocele patients can be recognised by computer tomography (CT) and magnetic resonance imaging techniques [2]. These abnormalities are commonly repaired surgically [3,8]. In animals, the meningoencephalocele has also been described in other domestic animals such as pigs, dogs and cats [7,[9][10][11].…”
mentioning
confidence: 99%
“…In humans, various types of meningoencephalocele patients can be recognised by computer tomography (CT) and magnetic resonance imaging techniques [2]. These abnormalities are commonly repaired surgically [3,8]. In animals, the meningoencephalocele has also been described in other domestic animals such as pigs, dogs and cats [7,[9][10][11].…”
mentioning
confidence: 99%
“…4,9,19,20 Kai et al, in 1996, reported a successful open repair using the transbasal intraand extradural approach. 21 A combined transcranial and transpalatal approach has been described, but in general intracranial approaches have decreased with the development of advanced endoscopic techniques. 22 Transnasal endoscopic techniques have rapidly evolved, and the expanded endonasal approach is now advocated for benign and malignant tumors as well as congenital and acquired defects of the skull base.…”
Section: Discussionmentioning
confidence: 99%